The Effect of Internet-Based Psychoeducation on Decreasing Academic Cheating in High School Students - Rohimatus Syahadah Muslimah; Ananta Yudiarso (Psikostudia : Jurnal Psikologi, 2023)
Academic cheating is an educational problem in Indonesia today. Almost every student in every educational institution commits fraud in the form of cheating, taking small notes on exams, copying, and pasting from the internet, and other cheating practices either by themselves or by friends. Therefore, there is a need for serious handling of this problem. One effort that can be made is to provide psychoeducation to students. The purpose of this study was to determine whether the provision of Internet-based psychoeducation can reduce instances of academic cheating, the effectiveness of various teacher monitoring methods, and the causes that lead to cheating. 11 students from four different regions participated in this experiment aged around 16-18 years. An online survey of students served as the instrument. Descriptive statistics are used for the analytical method. This study shows that engaging in online conversations about academic cheating can change participants' perceptions of this practice, thereby reducing their tolerance for it. The results of the average decrease between the pre-test and post-test were 91,818 and after psychoeducational interventions were 90,273, indicating that after engaging in online discussions, students were better able to understand and defend the central idea of the discussion that academic cheating is an unethical activity. Participants gain a deeper understanding of why any kind of academic cheating is wrong and how to prevent it. Therefore, it is important for all educators and parents to prevent and overcome academic fraud committed by students at school.Kecurangan akademik menjadi masalah pendidikan di Indonesia saat ini. Hampir setiap siswa di setiap lembaga pendidikan melakukan kecurangan dalam bentuk menyontek, membuat catatan kecil saat ujian, menyalin dan menempel dari internet, dan praktik menyontek lainnya baik oleh diri sendiri maupun teman. Oleh karena itu, perlu adanya penanganan yang serius mengenai permasalahan ini. Salah satu upaya yang dapat dilakukan adalah dengan memberikan psikoedukasi pada siswa. Tujuan dari penelitian ini adalah untuk mengetahui apakah pemberian psikoedukasi berbasis internet dapat mengurangi contoh kecurangan akademik, efektivitas berbagai metode pemantauan guru, dan penyebab yang mengarah pada kecurangan. 11 siswa dari empat daerah berbeda berpartisipasi dalam eksperimen ini usia sekitar 16-18 tahun. Sebuah survei online siswa berfungsi sebagai instrumen. Statistik deskriptif digunakan untuk metode analisis. Studi ini menunjukkan bahwa terlibat dalam percakapan online tentang kecurangan akademik dapat mengubah persepsi peserta tentang praktik ini, sehingga mengurangi toleransi mereka terhadapnya. Hasil penurunan rata-rata antara pre-test dan post-test sebesar 91.818 dan sesudah intervensi psikoedukasi sebesar 90.273, sehingga menunjukkan bahwa setelah terlibat dalam diskusi online, siswa lebih mampu memahami dan mempertahankan ide sentral diskusi bahwa menyontek akademik adalah kegiatan yang tidak etis. Para peserta memperoleh pemahaman yang lebih dalam tentang mengapa segala jenis kecurangan akademik itu salah dan bagaimana mencegahnya. Oleh karena itu, penting bagi seluruh tenaga pendidik dan orang tua untuk mencegah dan mengatasi adanya kecurangan akademik yang dilakukan oleh siswa di sekolah.